Analysis of the Empowerment of Hands Up Community Members in Creative Industries in Mataram City, West Nusa Tenggara Province - Ivan Suaidi; Muhammad Fauzan Azhmy (Institute of Computer Science (IOCS), 2022)
This study aims to determine the perception of members of member empowerment and the influence of empowerment on the creative industry. This research is qualitative research with a case study approach. The research subjects were 20 members of the Hands Above Community (TDA), in the city of Mataram. Data was collected through interviews with participants, researchers made observations and made document reviews to get an overview of empowerment activities in the Hands Above Community (TDA). The research data were analyzed by classifying the data based on the variety of existing data, then connecting them with data and information obtained from literature, documents, surveys, interviews, and field observations.The results of the analysis show that member empowerment as action refers to a process of self-empowerment and support that enables members to overcome feelings of powerlessness. Members have views on member empowerment, namely: 1) responsibility which means assuming all obligations and workloads by existing boundaries, 2) initiative which means members can decide and find what to do, 3) creativity where members explore their ideas about what their duties are, 4) direct participation is part of the involvement of members, 5) delegate authority to provide data and information to other members and entrust responsibilities. members feel the positive impact of member empowerment, namely: 1) members are motivated, become more creative, motivation is energy and strength, 2) responsive and adaptive which means members pay attention to the value of work and believe that what they do is important, 3) contribution means the role and participation of members in the community, 4) communication results in better relations between members and the process of exchanging facts, ideas, opinions, 5) potential that focuses on the ability of members to carry out their roles. Negative impacts felt by members: 1) lack of supervision and evaluation which has an impact on the final result